(untitled) (Research, Society and Development, 2021)
Pregnancy-related low back pain does not claim a well-defined etiology. Low back pain is frequent in pregnancy, especially during the third semester of pregnancy, as it is a period in which there is a greater physiological and anatomical change in the pregnant woman’s body. The study aimed to search in the literature for evidence on the performance and effectiveness of physical therapy in reducing pain in pregnant women with low back pain. A systematic review was carried out in the following databases: SCIELO, Virtual Health Library (VHL), PUBMED and PEDro, using the descriptors Physiotherapy, Pregnancy, Back Pain; Pregnancy; including complete articles, available in Portuguese, English or Spanish, published between 2010 and 2020. After careful analysis of the results obtained, 10 articles were selected for the preparation of the research. It was possible to observe that the authors focused mainly on exercises for low back pain, followed by transcutaneous electrical nerve stimulation (TENS) for analgesia. It is concluded that this study demonstrated that physiotherapy can be performed in pregnant patients with low back pain safely and effectively. The need for more studies in the area is highlighted, such as clinical trials, which provide more evidence on the role of physical therapy in pregnant women with low back pain, as well as the performance of national studies, considering that the vast majority of studies are international.